UV-B Radiation in the Acclimatization Mechanism of Psidium guajava in Sunlight - Campos, Felipe G. [UNESP]; Dantas, Mariana O. [UNESP]; Santos, João P. M. [UNESP]; Froes, Sophia S. [UNESP]; Gama, João P. S. [UNESP]; Boaro, Carmen S. F. [UNESP] (MDPI, 2023)
The ozone layer (O3) is essential to the absorption and blocking of UV-B radiation, preventing a large portion from reaching the Earth’s surface. The degradation of the ozone layer (O3) caused by increased pollution has led to climate change exerting significant influence on natural ecosystems and has resulted in severe stress on the environment, such as an increase in UV-B radiation, which has deleterious effects on plant physiology. UV-B influences the protection pathways that increase compound production, leading to metabolic adjustments and promoting plant acclimatization. This study evaluated whether UV-B application prior to sunlight exposure induces anthocyanin synthesis, photochemical change, and carbohydrate profile modification, contributing to acclimatization in Psidium guajava seedlings. A higher concentration of H2O2 may have stimulated anthocyanin synthesis. Furthermore, greater instantaneous water use efficiency (iWUE), the absence of trehalose—a stress marker, and lower concentrations of glucose, fructose, and sucrose indicate that these plants acclimatize when exposed to full sun (30 days). Seedlings exposed to increased UV-B may be more resistant to the climate. The radiation can aid in water resource management with elevated carbohydrate concentrations. These conditions may enhance the success of P. guajava in the field. Therefore, it is suggested that UV-B application to seedlings of P. guajava promotes effective acclimatization, as it activates anthocyanin synthesis, inhibits trehalose accumulation, and increases iWUE. UV-B radiation, depending on its radiance, can be used as a technique in seedling production that can be implanted in anthropic environments.
Keywords: carbohydrate profile; chlorophyll a/b; fluorescence of chlorophyll a; gas exchanges; phenolic compounds; plant defense